Comparison of palm oil esters production using immobilized lipases RM 1M and TL 1M - Kassim, Mohd Azlan (2012)
Palm oil esters (POE) were synthesized via enzymatic alcoholysis of palm oil fractions with oleyl alcohol using commercialized immobilized lipase as biocatalysts. The research focused on attempting to produce POE in a larger scale and reducing the production cost by replacing Lipozyme RM IM with Lipozyme TL IM which is 6 times cheaper as the alternative biocatalyst. The reaction condition used was based on the optimized condition of Lipozyme RM IM. Optimization was conducted in 2-L Stirred Tank Reactor (STR) using one parameter at a time approach. The optimum alcoholysis condition for Lipozyme TL IM in 2-L STR was: amount of palm oil 600 mmol, amount of oleyl alcohol 1800 mmol, amount of enzyme 24.7wt% of palm oil, temperature 60°C,reaction time 3 h and impeller speed 275 rpm. Using the optimum condition for production of POE using Lipozyme RM IM and Lipozyme TL IM, the reaction was scaled-up from lab scale (2-L STR) to higher scale production (15-L, 75-L and 300-L STR). For scale up using Lipozyme RM IM, the production was successfully scaled-up from 2-L to 15-L STR with similar result, But with production size of 300-L STR, the yield was reduced to 10%. Reduction of yield was also observed when Lipozyme TL IM was used. The yield decreased 13% during up scaling from 2-L to 15-L STR and another 30% from 15-L to 75-L STR. The transfer of downstream processing of the POE produced from the conventional separating funnel to stirred tank reactor to perform liquid-liquid extraction process was also investigated. The extraction condition was adopted from previous study. Effect of the impeller speed was studied and showed that there was no significant increment in percentage of extraction of oleyl alcohol with increase of impeller speed from 150-300 rpm. Effect of extraction cycle showed that palm oil esters were purified completely with 4 extraction steps. In the first extraction step, 65% of oleyl alcohol was successfully extracted. A kinetic study of the alcoholysis reaction of palm oil and oleyl alcohol using Lipozyme TL IM was conducted in a 2-L STR with the proposed mechanism of Ping-Pong Bi-Bi. Within the substrate concentration studied, the reaction obeyed the proposed mechanism without inhibition from the substrate (Vmax = 32.7 mmol/min, Km(Palm Oil) = 0.3147 mmol/ml, Km(Oleyl Alcohol) = 0.9483 mmol/ml). Thermodynamic parameters were as follows: ?H0 = 16 803.402 J/mol, ?S0 = 72.039 J.mol-1.K-1, Activation Energy, Ea = 16 850.396 J/mol.